2021
DOI: 10.2196/18079
|View full text |Cite
|
Sign up to set email alerts
|

User-Centered Design Process of an mHealth App for Health Professionals: Case Study

Abstract: Background User-centered design processes are infrequently employed and not fully explored for building mobile health (mHealth) apps that are particularly targeted to health professionals as end users. The authors have used a user-centered design–based approach to build an mHealth app for health professionals, tasked to deliver medical laboratory-related information on a daily basis. Objective Our objective is to generate a simple and functional user-ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 21 publications
0
32
0
2
Order By: Relevance
“…The fact that participants who were previously naive about the PedAMINES app were able to use it correctly to significantly reduce medication error rates [ 32 , 33 ] after a single 5-minute prescenario training and broadly agree on its usability validated the user-centered design [ 58 - 60 ], the Fitts laws [ 61 ], and progressive disclosure [ 62 ] principles that underpinned its iterative development process [ 63 ]. This approach has proven beneficial in allowing end users to influence the development process and increase the final usability of web-based HIT [ 64 , 65 ]. To provide some perspective, the mean total SUS scores >89 in this study were higher than those reported in a comparative study of the top 10 nonmedical mobile apps evaluated by >3500 users [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that participants who were previously naive about the PedAMINES app were able to use it correctly to significantly reduce medication error rates [ 32 , 33 ] after a single 5-minute prescenario training and broadly agree on its usability validated the user-centered design [ 58 - 60 ], the Fitts laws [ 61 ], and progressive disclosure [ 62 ] principles that underpinned its iterative development process [ 63 ]. This approach has proven beneficial in allowing end users to influence the development process and increase the final usability of web-based HIT [ 64 , 65 ]. To provide some perspective, the mean total SUS scores >89 in this study were higher than those reported in a comparative study of the top 10 nonmedical mobile apps evaluated by >3500 users [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, not all users used the instruction manual to understand the apps as some of them preferred to try a few times and be able to understand the functionality of the app [33]. Nevertheless, by having a manual it provided advantages to the users an option to read for better understanding of the app even to the professional users [34]. Hence, to improve the understanding of KEPT apps, a user's manual will be added at the top right corner for the users' better accessibility.…”
Section: Discussionmentioning
confidence: 99%
“…Health system assessment tools and frameworks can help structure the review of the current obstacles and facilitators surrounding CVD prevention and care [ 100 101 ], which often require a mixed-methods approach. User-centred and co-design principles are necessary to contextualise interventions and make them more effective [ 102 103 ]. The World Wide Web Consortium summarised the user-centred design process [ 104 ], which outlines clear steps in the (co)-design of applications.…”
Section: Roadblocks and Solutions To Implement Digital Health Interve...mentioning
confidence: 99%